Pengaruh Motivasi Investasi, Pengetahuan Investasi, dan Media Sosial Terhadap Minat Investasi Pasar Modal Pada Mahasiswa - Santoso, Victor Devin; Sasongko, Noer (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to examine the effect of investment motivation, investment knowledge, and social media on capital market investment interest in students. The type of research used is quantitative causality. The population used in this study are students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta semester 6, semester 8, and semester 10 with a total of 3001 students. The technique used in this study is Purposive Sampling. The Data used is primary data data in the form of responses obtained through questionnaires distributed to respondents. The data analysis technique used in this study is multiple linear regression analysis. The results of this study showed that investment motivation, investment knowledge and social media affect investment interest.